Recurrence of chronic encapsulated hematoma following cyst formation after stereotactic radiosurgery for brain arteriovenous malformations: a case report - Iñigo L. Sistiaga; Gregorio Catalán-Uribarrena; Silvia Gamba; Alejandro Carrasco; Laura Zaldumbide; Lorena Mosteiro; Iñigo Pomposo (Chinese Neurosurgical Journal)
Abstract Background Delayed radiation-induced complications after stereotactic radiosurgery (SRS) for arteriovenous malformations (AVM) have scarcely been described in the literature, and their incidence, pathophysiology, and treatment remain unclear. Additionally, the literature regarding these complications is confusing. The authors present a well-documented case report describing these late complications, adding evidence to the possible common pathophysiological mechanism underlying them, and illustrating an effective treatment modality when they occur. Case presentation A case of a 28-year-old male with an increasing cyst formation (CF) appearing 10 years after SRS for AVM is presented. Despite surgical treatment, due to the incomplete resection of the angiomatous nodule, recurrence as a chronic encapsulated expanding hematoma (CEEH) occurred. This relapse required a second treatment, which could have been avoided if aggressive surgical treatment had been performed initially. Conclusions This case highlights the continuum between CF and CEEH, challenging existing confusion in the literature. Complete resection of the angiomatous nodule associated with CF is imperative for achieving resolution and preventing recurrence.